How South Korea Represents Japan as Colonization in Film - Azhari; Cristian Zamir Sierra Echeverria; Muhammad Zikrullah (Winaya Inspirasi Nusantara Foundation, 2025)
The advancement of the movie industry makes it undeniable that wars between countries have occurred until now. It's just that the way of fighting is different. This study can conceptually illustrate the strategy of a country to attack another country by reconstructing the country's image negatively. The purpose of this study is to understand the representation of Japan as a colonizer in a Korean film entitled